Pengurusan insurans dalam industri pembinaan di Malaysia - Ismail, Fadzida (2005)
This study aims to get the insight into the insurance application in the Malaysian construction industry. Sufficient insurance coverage is important to protect an organisation’s resources and finance. Insurance companies develop their resources through the insurance premium. The significance of insurance management in the construction industry is to provide security and to increase the chances of gaining back the losses occurred in any contracted incidents. The objectives of the research are to identify the factors that affect the premium price, to study the types of claims arise from construction activities and to identify the claim procedure. To find all the answers to the above objectives, questionnaire surveys have been distributed to contractors and insurance companies, and semi-structured interviews were also performed with experts and insurance companies’ representatives. Finally, this research gives suggestion on the action that can be implied by the contractors in order to minimise the incidents at site.